Gestão ambiental na indústria da saúde no Brasil: a gestão da cadeira produtiva em favor da sustentabilidade ambiental - Ribeiro Filho, Vital de Oliveira (2005)
The health assistance sector has been put under pressure for improvements in the waste management and in other environmental aspects. In Brazil, actions in this area have been limited by a lack of resources and knowledge. Although the search for treatment systems for health care services dangerous residues increases progressively, less onerous and more rational measures, involving reduction or residue recycling, are not as widespread it should. In this work, we analyze the health industry value chain, highlighting health care services and their relations with levels above and below, with the aim of identifying aspects that ease or hinder improvements in the environmental performance of the sector. This analysis was compared to some of the most used managerial environmental administration models and to two successful international projects (“Health Care Without Harm” and “Hospitals for a Health Environment”). We conclude with the suggestion that, these models as much as the successful experiences, require cooperation and integration along the productive chain and that other studies are necessary to subsidize the optimization of these findings and to establish models for the integrated development of environmental sustainability in health care sector in Brazil.